Predictive factors for the efficacy of brolucizumab in refractory polypoidal choroidal vasculopathy following aflibercept resistance - Akie Yoshinaga; Kohdai Kitamoto; Shuichiro Aoki; Ryo Terao; Tatsuya Inoue; Ryo Obata; Keiko Azuma (PLoS ONE, 2025)
Purpose To identify predictors of extension of the injection interval beyond 8 weeks at the 24-month visit after switching to brolucizumab in aflibercept-resistant polypoidal choroidal vasculopathy (PCV). Design Retrospective observational study Methods 17 eyes of 16 patients with persistent or recurrent exudation on aflibercept were switched to intravitreal brolucizumab and managed with a treat-and-extend (T&E) regimen with a minimum 8-week interval after loading. The primary outcome contrasted extension (>8 weeks) versus non-extension (≤8 weeks) at month 24. Prespecified predictors were early central choroidal thickness (CCT) change from baseline to the switch visit (A0 to A1; ≥ 40% reduction) and pachychoroid. Associations were tested with Fisher’s exact tests and Firth-penalized logistic regression with the event defined as extension. Results At 24 months, 6 of 17 eyes (35%) achieved extension. A ≥ 40% early CCT reduction occurred in 0 of 6 extension eyes versus 7 of 11 non-extension eyes (Fisher exact two-sided P ≈ 0.035). In the Firth model (event = extension), < 40% CCT reduction strongly predicted extension (odds ratio 38.5; profile-likelihood 95% CI 2.0–10,000; LR P = 0.004). Non-pachychoroid showed the same direction with wide CIs (odds ratio 14.3; 95% CI 0.99–2,174; LR P = 0.006). Model fit was significant (LR χ² = 15.19, P = 0.0005) and discrimination was good (apparent AUC ≈ 0.97). We prespecified a parsimonious two-predictor model to limit overfitting; adding age, sex, prior photodynamic therapy, or number of prior aflibercept injections did not materially change coefficients or improve AICc (ΔAICc < 2). Conclusions Eyes without marked early choroidal thinning (<40% CCT reduction at A1) were more likely to extend, whereas marked thinning (≥40%) signaled difficulty extending under T&E regimen after switching to brolucizumab. Given the small sample and few events, estimates should be interpreted cautiously and considered hypothesis-generating, and warrant prospective external validation studies.